The puzzle of the Swiss interest rate island: Stylized facts and a new interpretation - Peter Kugler; Beatrice Weder (Hamburg Institute of International Economics (HWWA), 2002)
This paper contributes to the debate about the puzzle of the Swiss Interest Rate Island. It starts out by establishing some stylized facts about the nature of the puzzle. First it shows that long run real returns on Swiss Euro Deposits have been significantly lower than in any other major currency. A decomposition of return differentials into deviations from uncovered interest rate parity and deviations from purchasing power parity reveals that the former contributes most to the puzzle. Two implications follow from these stylized facts: (i) since the puzzle is present in Euro Deposit rates it cannot be due to local factors such as banking secrecy, and (ii) solutions to the puzzle have to provide an explanation for a long run failure of uncovered interest rate parity rather than for real appreciation. Historical evidence is presented that suggests the puzzle may be attributed to a reverse peso problem. The paper discusses the consequences of this interpretation for Swiss monetary and exchange rate policy. – – Diese Arbeit leistet einen Beitrag zu der Debatte über das Rätsel ?Zinsinsel Schweiz? indem es stilisierte Fakten über die Natur dieses Rätsels dokumentiert. Als erstes wird aufgezeigt, dass die langfristigen realen Erträge auf Schweizer Euro Einlagen deutlich niedriger waren als in anderen Hauptwährungen. Eine Zerlegung der Ertragsunterschiede in Abweichungen von der ungedeckten Zinsparität und Abweichungen von Kaufkraftparität enthüllt, dass der erste Faktor den Hauptanteil am Rätsel trägt. Zwei Folgerungen ergeben sich daraus: (i) nachdem sich dieses Rätsel in Euro Einlagen zeigt, kann es nicht durch nationale Eigenschaften wie z.B. das Bankgeheimnis verursacht werden, und (ii) Lösungen für dieses Rätsel müssen eine Erklärung für das langfristige Versagen der ungedeckten Zinsparität liefern und nicht für die reale Wertsteigerung. Aufgrund von historischen Datenreihen folgern wir, dass das Rätsel auf ein ?Peso Problem? zurückzuführen ist und diskutieren die Konsequenzen für die schweizerische Geld- und Wechselkurspolitik.
Keywords: G15; E43; E44; 330; Realzins; Zinsparität; Kaufkraftparität; Risikoprämie; Schätzung; Schweiz; EU-Staaten; Peso problem